1997
DOI: 10.1183/09031936.97.10071576
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and health-related quality of life in patients with obstructive airways disease

Abstract: This study evaluated the effects of body weight and lean mass abnormalities on health-related quality of life (HRQL) in obstructive airways disease.Body weight, lean mass (using dual-energy X-ray absorptiometry), and HRQL (using the St George's Respiratory Questionnaire (SGRQ)) were measured in 50 patients. Low lean mass was defined as a lean mass index (lean mass/height 2 ) below the fifth percentile of a control population. Dyspnoea was measured by the baseline dyspnoea index.The mean (SD) age was 69±9 yrs; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
75
7
13

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(103 citation statements)
references
References 15 publications
8
75
7
13
Order By: Relevance
“…In our much larger cohort, we found similar results with pectoralis muscle area being significantly inversely associated with MMRC and SGRQ. We, however, did not find an association between BMI and either MMRC or the SGRQ, possibly because of the previously documented nonlinear relationship between weight and health-related quality of life measures (26). This is in keeping with findings from Mostert and colleagues (27), who found that patients with COPD who lost fat-free mass irrespective of body weight had greater impairment in 12MWD, handgrip strength, and SGRQ.…”
Section: Original Researchsupporting
confidence: 75%
“…In our much larger cohort, we found similar results with pectoralis muscle area being significantly inversely associated with MMRC and SGRQ. We, however, did not find an association between BMI and either MMRC or the SGRQ, possibly because of the previously documented nonlinear relationship between weight and health-related quality of life measures (26). This is in keeping with findings from Mostert and colleagues (27), who found that patients with COPD who lost fat-free mass irrespective of body weight had greater impairment in 12MWD, handgrip strength, and SGRQ.…”
Section: Original Researchsupporting
confidence: 75%
“…Our results did not show a relationship between body composition attributes and HRQoL. Shoup et al (23) showed that the weight variable was not significantly related to the SGRQ symptom score; however, underweight patients had significantly greater impairment in activity, impact, and total scores than did normal weight patients. In the same study, overweight patients had more impairment in the SGRQ impact and total scores than did normal weight patients.…”
Section: Discussionmentioning
confidence: 37%
“…Fifty-three per cent of the women and 76% of the men had an FFMI lower than reference values. A low fat-free mass has been shown to impair exercise performance (31,32), reduce health-related quality of life (33) and increase mortality (16,34). COPD, in advanced stages of the disease, means frequent hospital admissions and also in some cases a long duration of hospital stay.…”
Section: Discussionmentioning
confidence: 99%